MATLAB and Simulink resources for Arduino, LEGO, and Raspberry Pi

Learn moreOpportunities for recent engineering grads.

Apply Today
Asked by tejas grewal on 18 Jul 2013

I have 6 coupled pde (mass balance eqn for 6 component coupled through rate of reaction Ri)of type:

dFi/dt = dFi/dz + Ri with initial condition: Fi(0,z) = 0

boundary cond. Fi(t,0) = Fi0

i tried using method of lines

initial cond.

F0 = [FinE repmat(0,Z-1); % FinE inlet flow rate of ethanol

FinW repmat(0,Z-1); % Finw inlet flow rate of water

zeros(1,Z) % products inlet flow rate zeros(1,Z) zeros(1,Z) zeros(1,Z)] tspan = linspace(0,0.2,N) [t,F] = ode45('rates',tspan,F0) ****************************************** function dFdt = rates(t,F) i = 1 k1 = k01*exp(-Ea1/RT) k1'= ...

dFdt(i,:) = (-((F(i,:)-FinE)./(dx(1,1)*Area))+eta*(-k1*F(i+1,:)*F(i,:)+k3*F(i+3,:))

dFdt(i+1,:) = (-((F(i+1,:)-Finw)./(dx(1,1)*Area))+eta*(-k1*F(i+1,:)*F(i,:))

dFdt(i+2,:) = (-((F(i+2,:)-0)./(dx(1,1)*Area))+eta*(k1*F(i+1,:)*F(i,:)+k2*F(i+4,:))

dFdt(i+3,:) = ...

dFdt(i+4,:) = ....

dFdt(i+5,:) = ....

i = 7:6:6*Z-5

dFdt(i,:) = (-((F(i,:)-F(i-6,:))./(dx(1,1)*Area))+eta*(-k1*F(i+1,:)*F(i,:)+k3*F(i+3,:))

dFdt(i+1,:) = (-((F(i+1,:)-F(i-5,:))./(dx(1,1)*Area))+eta*(-k1*F(i+1,:)*F(i,:))

dFdt(i+2,:) = (-((F(i+2,:)-F(i-4,:))./(dx(1,1)*Area))+eta*(k1*F(i+1,:)*F(i,:)+k2*F(i+4,:))

dFdt(i+3,:) = ...

dFdt(i+4,:) = ....

dFdt(i+5,:) = ....

this code is giving NAN values for the above initial conditions but running with initial condition Fi(0,z) = Fi0 why is this so.. also if any one can suggest the alternative method to solve for Fi vs t as well as vs z

*No products are associated with this question.*

Answer by Deepak Ramaswamy on 19 Jul 2013

Edited by Deepak Ramaswamy on 19 Jul 2013

This is with regards to the second part of your question: This problem should be solvable via pdepe. I could not infer the form of Ri and the right BC is not specified. But the form for pdepe (check out pdepe doc for what below terms such as m, c, f, s etc. mean) would look something like:

m = 0

**c**

+- -+ | 1, 0, 0, 0, 0, 0 | | | | 0, 1, 0, 0, 0, 0 | | | | 0, 0, 1, 0, 0, 0 | | | | 0, 0, 0, 1, 0, 0 | | | | 0, 0, 0, 0, 1, 0 | | | | 0, 0, 0, 0, 0, 1 | +- -+

**f**

+- -+ | F1(z, t) | | | | F2(z, t) | | | | F3(z, t) | | | | F4(z, t) | | | | F5(z, t) | | | | F6(z, t) | +- -+ *s*

+- -+ | R1(F1(z, t), F2(z, t), F3(z, t), F4(z, t), F5(z, t), F6(z, t)) | | | | R2(F1(z, t), F2(z, t), F3(z, t), F4(z, t), F5(z, t), F6(z, t)) | | | | R3(F1(z, t), F2(z, t), F3(z, t), F4(z, t), F5(z, t), F6(z, t)) | | | | R4(F1(z, t), F2(z, t), F3(z, t), F4(z, t), F5(z, t), F6(z, t)) | | | | R5(F1(z, t), F2(z, t), F3(z, t), F4(z, t), F5(z, t), F6(z, t)) | | | | R6(F1(z, t), F2(z, t), F3(z, t), F4(z, t), F5(z, t), F6(z, t)) | +- -+

pLeft (p for left BC)

+- -+ | F1(z, t) - F0 | | | | F2(z, t) - F0 | | | | F3(z, t) - F0 | | | | F4(z, t) - F0 | | | | F5(z, t) - F0 | | | | F6(z, t) - F0 | +- -+ qLeft (q for left BC)

+- -+ | 0 | | | | 0 | | | | 0 | | | | 0 | | | | 0 | | | | 0 | +- -+

## 0 Comments